Hepatic Macrophages in Liver Injury - Shan, Zhao; Ju, Cynthia (Frontiers in Immunology, 2020)
Ample evidence suggests that hepatic macrophages play key roles in the injury and repair mechanisms during liver disease progression. There are two major populations of hepatic macrophages: the liver resident Kupffer cells (KCs) and the monocyte-derived macrophages (MoMɸs), which rapidly infiltrate the liver during injury. At different disease conditions, the tissue microenvironmental cues of the liver critically influence the phenotypes and functions of hepatic macrophages. Furthermore, hepatic macrophages interact with multiple cells types in the liver, such as hepatocytes, neutrophils, endothelial cells, and platelets. These crosstalk interactions are of paramount importance in regulating the extents of liver injury, repair and ultimately liver disease progression. In this review, we summarize the novel findings highlighting the impact of injury-induced microenvironmental signals that determine the phenotype and function of hepatic macrophages. Moreover, we discuss the role of hepatic macrophages in homeostasis and pathological conditions through crosstalk interactions with other cells of the liver.